Contours of death and disease in early modern England - Dobson, Mary J. (Cambridge University Press, 1997)
Using a wide range of sources for the south-east of England, Dobson highlights the tremendous variation in levels of mortality across geographical contours and across two centuries, exploring the causes and consequences of these variations.
Keywords: Sussex; Diseases -- England, South East -- History -- 17th century.; Diseases -- England, South East -- History -- 18th century.; Mortality -- England, South East -- History -- 17th century.; Mortality -- England, South East -- History -- 18th century.; Diseases -- England, South East -- Statistics.; Mortality -- England, South East -- Statistics.; Medical geography -- England, South East.; Medicine -- History -- 17th century.; Medicine -- History -- 18th century.; Mortality.; Disease Outbreaks -- history; History, 17th Century; History, 18th Century; Mortality; England; Maladies -- Angleterre (Sud-Est) -- Histoire -- 17e siècle.; Maladies -- Angleterre (Sud-Est) -- Histoire -- 18e siècle.; Mortalité -- Angleterre (Sud-Est) -- Histoire -- 17e siècle.; Mortalité -- Angleterre (Sud-Est) -- Histoire -- 18e siècle.; Maladies -- Angleterre (Sud-Est) -- Statistiques.; Mortalité -- Angleterre (Sud-Est) -- Statistiques.; Géographie médicale -- Angleterre (Sud-Est); Médecine -- Histoire -- 17e siècle.; Médecine -- Histoire -- 18e siècle.; Mortalité.; mortality.; MEDICAL -- Health Risk Assessment.; MEDICAL -- Epidemiology.; Medicine; Diseases; Medical geography; England -- England, South East; Bevölkerung; Krankheit; Todesursache; Sterblichkeit; Kent; Essex; England -- Südost; Ziekten.; Sterfte.; Épidémiologie -- Grande-Bretagne (sud-est) -- 1500-1800.; Mortalité -- Grande-Bretagne (sud-est) -- 1500-1800.; Maladies -- Grande-Bretagne (sud-est) -- 1500-1800.; Santé et hygiène -- Grande-Bretagne (sud-est) -- Histoire.; Geschichte (1600-1800); Geschichte 1600-1800.; 1600-1799; History; Statistics